US INTERESTS IN CENTRAL ASIA: REGIONAL SECURITY - Shukurov Shuxrat Zaynievich (Web of Journals Publishing, 2025)
This paper examines the United States' strategic interests and security objectives in Central Asia. It explores the region's geopolitical significance, emphasizing the importance of energy resources, counter-terrorism efforts, and the maintenance of regional stability. The study also analyzes how U.S. foreign policy navigates challenges posed by competing global players, such as Russia and China, within the security framework of Central Asia. The findings contribute to a deeper understanding of the interplay between political, economic, and security issues that shape U.S. strategy in this critical region.
Keywords: US interests, Central Asia, regional security, geopolitics, energy resources, counter-terrorism, foreign policy, global competition, strategic stability.